1980
DOI: 10.1530/acta.0.0940064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenylbutazone on thyroid iodine metabolism in vitro

Abstract: Several alterations of thyroid function parameters have been reported in patients treated with phenylbutazone and we have studied the effect of this drug on the intrathyroidal iodine metabolism. An inhibition of the iodide transport expressed in terms of T/M ratios was observed in bovine thyroid slices incubated with high phenylbutazone concentrations. 10\m=-\3m produced 72% inhibition whereas lower concentrations showed no significant difference as compared with controls. Iodotyrosine synthesis was affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…No significant variation in the T/M was found from stages I to V and the adult. The T/M values obtained in this study were markedly lower than some previously reported (33)(34)(35) although in a range similar to others (22,36,37). No explanation could be found for these dif¬ ferences.…”
Section: Iodide Transport and Organificationsupporting
confidence: 56%
“…No significant variation in the T/M was found from stages I to V and the adult. The T/M values obtained in this study were markedly lower than some previously reported (33)(34)(35) although in a range similar to others (22,36,37). No explanation could be found for these dif¬ ferences.…”
Section: Iodide Transport and Organificationsupporting
confidence: 56%